(untitled) (Revista de Ciências Agroveterinárias, 2019)
This study aimed to evaluate the microbiological patterns of salmon sushi and sashimi sold in specialized restaurants located in the city of Pelotas, Rio Grande do Sul, Brazil. Twenty samples were analyzed (10 sushi and 10 sashimi) and submitted to Salmonella testing and counting of fecal coliforms, coagulase-positive Staphylococcus and Vibrio parahaemolyticus. One observed 70% of the samples were at odds with the standards established by the Brazilian law. The results indicate the need for more care about the quality of the raw material and for hygiene and sanitary measures when preparing and handling the product, also considering that these foods are consumed without cooking, which increases the risk of contamination.